Detection of Enteropathogenic Esherichia coli (EPEC) by Serotyping and Cell Adhesion Assay among Children in North-Eastern Peninsular Malaysia: A Hospital Based Study - Haq, J Ashraful; Li, Hin Choon; Rahman, Rosliza Abdur (Ibrahim Medical College Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Enteropathogenic Escherichia coli (EPEC) is a major cause of diarrhea in children below 5 years of age in the developing countries. The present study investigated the role of EPEC in childhood diarrhea among the patients attending a university hospital in north-eastern peninsular Malaysia by serotyping and cell adhesion assay using HEp-2 and HeLa cells. A total of 60 stools or rectal swabs from watery diarrhea cases and 16 age matched healthy controls were examined. EPEC were isolated from 14 (23.3%) diarrhea cases and from 1 (9.1%) control by serotyping. Of the 14 EPEC strains, the predominant strain was 0125: K70 (28.5%). Cell adhesion assay detected 26.6% and 30.0% adherent Escherichia coli (E. coli) in diarrhea cases by HEp-2 and HeLa system respectively. Three adherence patterns were noted namely localized, diffuse and aggregative patterns. About 81- 88% of isolated E. coli exhibited diffuse adherence pattern by HEp-2 and HeLa cell assay respectively. About 43-44% E. coli exhibiting positive cell adherence phenotype with HEp-2 and HeLa cell assays tested negative with EPEC antisera. The findings indicate that EPEC is an important cause of childhood diarrhea in north-eastern peninsular Malaysia and cell adhesion assay is more sensitive than serotyping for detection of diarrheogenic E. coli. Ibrahim Med. Coll. J. 2008; 2(2): 40-43 Key Words: EPEC, diarrhea, serotyping, Malaysia doi: 10.3329/imcj.v2i2.2935